Analysis of Market Needs (Market Signal) in the Context of Developing Study Programs in the Department of Business and Hospitality - Rosalin, Sovia; Rudiyanto, San (Universitas Negeri Makassar, 2023)
This research was conducted to analyze labor market needs, ensure that business and hospitality department graduates reflect the needs of the world of work, and evaluate the suitability of study programs to these needs. The aim of this research is to analyze market signals that can produce graduate profiles that suit the needs of the global job market. Research also examines study programs that are relevant to the discipline and ensures suitability to industry demands. Research was conducted on business and hospitality companies in Malang City using descriptive analysis methods with subjectivity and theoretical aspects being the main focus. The research results show that educational qualifications, work experience through internships, additional certification, high GPA, college prestige, and language skills, especially English, remain determining factors in employee selection. Apart from that, the research adds a new variable that is not yet covered in the Job Marketing Signaling theory, namely grooming or appearance, as an element that has a significant influence on the company's perception of prospective employees.